Pengaruh Pembelajaran Berbatuan Geogebra terhadap Pemahaman Konsep Matematis ditinjau dari Gaya Kognitif - Purwanti, Ramadhani Dewi; Pratiwi, Dona Dinda; Rinaldi, Achi (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
The purpose of this research is to know whether there is influence of learning model of Geogebra-assisted Discovery Learning to understanding mathematical concept, to know whether there is influence between learners who have cognitive style of FI and FD to understanding mathematical concept, to know whether there is interaction between learning of Discovery Learning Unity Geogebra with the cognitive style of learners towards the understanding of mathematical concepts. This research type is quasi experiment research, population in this research is all students of class VII of SMP Negeri 2 Bandar Lampung, sampling technique in this research use class random technique where class VII-8 as experiment class 1 with study of Discovery Learning assisted geogebra, Class VII-7 as a control class with Discovery Learning learning with Microsoft Power Point. Technique of data analysis in this research use two way Anova test with unequal cell. Based on the test results, the first hypothesis is indicated by the statistical price of 8,871, so that H0A is rejected with the conclusion that there is influence of Discovery Learning learning by geogebra toward the understanding of mathematical concept. For the second second hypothesis is shown with a statistical price of 5.23 , so H0B is rejected with the conclusion that there is an influence between learners who have cognitive style of FI and FD on the understanding of mathematical concepts. For the third hypothesis, it is shown by the statistical price of 1.05, so H0AB is accepted with no conclusion there is no interaction between the learning of Geogebra-assisted Discovery Learning with the cognitive style of learners towards the understanding of mathematical concepts.